CBT4CBT web-based add-on treatment for cocaine use disorder: Study protocol for a randomized controlled trial - Mallorquí-Bagué, Núria; Palazón-Llecha, Alba; Madre, Mercè; Batlle, Francesca; Duran-Sindreu, Santiago; Trujols, Joan (Frontiers in Psychiatry, 2023)
Background Cocaine use disorder (CUD) is a chronic condition that presents high relapse rates and treatment dropouts. Web-based interventions have proven to be effective when optimizing face-to-face treatments in different mental health conditions and have the potential to optimize current CUD treatments. However, web-based interventions in addictive behaviors are still limited. The aim of this study is to evaluate whether adding a web-based cognitive behavioral therapy (i.e., CBT4CBT) to standard CUD treatment, improves treatment outcomes in a Spanish sample of patients with severe CUD (which requires inpatient treatment). Additionally, we aim to explore predictive factors of treatment response and treatment gender-related differences. Methods All individuals coming for inpatient cocaine detoxification who meet the inclusion criteria will have the possibility to be part of the study. The participants of this open-label randomized controlled clinical trial (RCT) will be allocated to treatment as usual (TAU) or TAU+CBT4CBT after the hospitalization for cocaine detoxification. During the inpatient treatment they will all receive an individualized psychological intervention. There will be six time point assessments: at 48–72 h of starting inpatient treatment, at the end of inpatient treatment and before starting day care and outpatient treatment, at the end of the 8 weeks CTB4CBT / TAU arm treatment and at three follow-up time points (1-, 3-, and 6-months post-treatment). Discussion To the best of our knowledge, this is the first RCT that explores the efficacy of adding a web-based cognitive behavioral therapy to usual CUD treatment with patients of a clinical sample in Europe. Trial registration IIBSP-CTB-2020-116, NCT05207228. Submitted 8th of April 2021, posted 26 st of January 2022. https://clinicaltrials.gov/ct2/show/NCT05207228?cond=Cocaine+Use+Disorder&draw=2&rank=1.